Artificial bone scaffold and preparation method thereof

By injecting amorphous calcium phosphate nanohybrid material into the polyvinyl alcohol stent to form an interlocking structure, the problem of low strength of artificial bone stent material is solved, high strength and step-by-step degradation is achieved, and osteogenesis ability and clinical application prospects are improved.

CN119733112APending Publication Date: 2025-04-01INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411914362.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, the artificial bone stent material has a low strength and is further reduced after degradation, which limits the growth and clinical application of new bones.

Method used

By injecting amorphous calcium phosphate nanohybrid material into the polyvinyl alcohol stent, it fills the pores of the stent and forms an interlocking structure, thereby improving the strength of the artificial bone stent.

Benefits of technology

The high strength of artificial bone stents (compression strength is above 40MPa) and step-by-step degradation are achieved, improving osteogenesis ability and clinical application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733112A_ABST
    Figure CN119733112A_ABST
Patent Text Reader

Abstract

The invention provides an artificial bone scaffold and a preparation method thereof, and relates to the technical field of biomedical materials.The preparation method comprises the following steps that an amorphous calcium phosphate nanometer hybrid material is poured into a polyvinyl alcohol scaffold, pores of the polyvinyl alcohol scaffold are filled with the amorphous calcium phosphate nanometer material, and the artificial bone scaffold is obtained; wherein the amorphous calcium phosphate nano hybrid material is obtained by mixing amorphous calcium phosphate, polycaprolactone and an organic solvent; the polyvinyl alcohol stent is obtained by mixing amorphous zinc phosphate, polyvinyl alcohol and glycerol, carrying out heat preservation treatment and then carrying out 3D printing. The pores of the polyvinyl alcohol scaffold are filled with the amorphous calcium phosphate nano material through perfusion to form an interlocking structure, so that the strength of the artificial bone scaffold is improved; step-by-step degradation can be realized through the amorphous calcium phosphate nano hybrid material and the polyvinyl alcohol scaffold, so that the osteogenic ability of the artificial bone scaffold is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to an artificial bone scaffold and a preparation method thereof. Background Art

[0002] As the aging process of my country's population accelerates and the incidence of orthopedic diseases rises rapidly, the market size of artificial bone, as an important bone repair material, has also grown. The number of osteoporosis patients in my country is close to 70 million, and about 3 million new bone injury patients are added each year. Most of these patients need to use artificial bone for treatment. It is reported that the scale of my country's artificial bone market will further expand. Bone tumors are a more complex and serious type of orthopedic disease. The cost of treating bone tumors in orthopedic clinics is 4-6 times that of common orthopedic diseases. However, bone tumor surgery is very traumatic, and complications such as infection, bleeding, nerve damage, and fracture nonunion may occur after surgery, and the cure rate is relatively low.

[0003] At present, bone cement or autologous bone filling is generally used after the resection of bone tumors, but due to the relatively large resection area, pain in the bone removal area will seriously affect the patient's recovery and quality of life. Recent related studies have shown that 3D printing technology can customize personalized artificial bones according to the patient's specific conditions, improving the accuracy and effect of surgery; however, the existing 3D printing technology, such as melt extrusion, light curing, etc., has many defects in the preparation of degradable artificial bone scaffold materials, and the strength of the scaffold material is relatively low (about 20MPa). At the same time, the strength of the scaffold is further reduced after degradation, causing the destruction of the original interconnected pore structure, which is not conducive to the growth of new bone, limiting the clinical application in the early stage. Summary of the invention

[0004] Therefore, the present invention provides an artificial bone scaffold and a preparation method thereof, which can solve the technical problem of low strength of artificial bone scaffold materials in the prior art.

[0005] In order to solve the above problems, the present invention provides a method for preparing an artificial bone scaffold, comprising the following steps:

[0006] The amorphous calcium phosphate nano-hybrid material is infused into the polyvinyl alcohol scaffold, so that the amorphous calcium phosphate nano-material fills the pores of the polyvinyl alcohol scaffold to obtain the artificial bone scaffold.

[0007] Furthermore, the amorphous calcium phosphate nano-hybrid material is prepared by the following method:

[0008] Mixing amorphous calcium phosphate, polycaprolactone and an organic solvent to obtain the amorphous calcium phosphate nano-hybrid material;

[0009] Wherein, the amorphous calcium phosphate is amorphous calcium phosphate nanoparticles.

[0010] Furthermore, the mass ratio of the amorphous calcium phosphate to polycaprolactone is 0.05-1:1; and / or

[0011] The mass ratio of the total mass of the amorphous calcium phosphate and the polycaprolactone to the mass of the organic solvent is 1:5-10; and / or

[0012] The particle size of the amorphous calcium phosphate is 10-500 nm; and / or

[0013] The number average molecular weight of the polycaprolactone is 36000-100000; and / or

[0014] The organic solvent is one or more of chloroform, dimethylformamide and dichloromethane.

[0015] Furthermore, the polyvinyl alcohol scaffold is prepared by the following method:

[0016] Amorphous zinc phosphate, polyvinyl alcohol and glycerol are mixed, and after heat preservation treatment, an amorphous zinc phosphate nano-hybrid material is obtained, and the amorphous zinc phosphate nano-hybrid material is 3D printed to obtain the polyvinyl alcohol scaffold;

[0017] Wherein, the amorphous zinc phosphate is amorphous zinc phosphate nanoparticles.

[0018] Further, the particle size of the amorphous zinc phosphate is 10-500 nm; and / or

[0019] In the amorphous zinc phosphate, the molar ratio of zinc ions to phosphate ions is 1.45-1.55; and / or

[0020] The alcoholysis degree of the polyvinyl alcohol is 80%-99%; and / or

[0021] The weight ratio of polyvinyl alcohol to glycerol is 0.5-4:1; and / or

[0022] The weight ratio of the amorphous zinc phosphate to the polyvinyl alcohol is 0.01-1:1.

[0023] Furthermore, during the 3D printing process: the printing temperature is 180°C-280°C; the extrusion speed is 0.05-0.5 mm / s; the moving speed of the print head is 1-15 mm / s; and / or

[0024] The porosity of the polyvinyl alcohol scaffold is 20%-80%.

[0025] Furthermore, after the step of 3D printing the amorphous zinc phosphate nano-hybrid material, the method further comprises:

[0026] heat treating the polyvinyl alcohol stent;

[0027] Preferably, the temperature of the heat treatment is 80-180°C;

[0028] Preferably, the heat treatment time is 6-72h.

[0029] Furthermore, the amorphous calcium phosphate nano-hybrid material is poured into the polyvinyl alcohol stent through a mold; wherein the amorphous calcium phosphate nano-hybrid material is in a molten state;

[0030] Preferably, before pouring, the amorphous calcium phosphate nano-hybrid material is heated to 60° C.-180° C.;

[0031] Preferably, the perfusion pressure is 0.1-2MPa;

[0032] Preferably, the perfusion time is 0.1-3h.

[0033] On the other hand, the present invention provides an artificial bone scaffold, the artificial bone scaffold comprising a polyvinyl alcohol scaffold and an amorphous calcium phosphate nano-hybrid material infused into the pores of the polyvinyl alcohol scaffold;

[0034] The compressive strength of the artificial bone scaffold is above 40MPa;

[0035] The degradation time of the artificial bone scaffold is 12-24 months.

[0036] Furthermore, the artificial bone scaffold is obtained by any of the preparation methods described above.

[0037] Compared with the prior art, the artificial bone scaffold and the preparation method thereof provided by the present invention have at least the following beneficial effects:

[0038] 1. The present invention provides a method for preparing an artificial bone scaffold, comprising: injecting an amorphous calcium phosphate nano-hybrid material into a polyvinyl alcohol scaffold, so that the amorphous calcium phosphate nano-material fills the pores of the polyvinyl alcohol scaffold to obtain an artificial bone scaffold; based on the above method, the present invention fills the pores of the polyvinyl alcohol scaffold with the amorphous calcium phosphate nano-material by injection to form an interlocking structure, thereby improving the strength of the artificial bone scaffold.

[0039] 2. Furthermore, the amorphous calcium phosphate nano-hybrid material of the present invention is obtained by mixing amorphous calcium phosphate nano-particles, polycaprolactone, and an organic solvent; the polyvinyl alcohol scaffold of the present invention is obtained by mixing amorphous zinc phosphate nano-particles, polyvinyl alcohol, and glycerol, and obtaining an amorphous zinc phosphate nano-hybrid material after heat preservation, and then 3D printing the amorphous zinc phosphate nano-hybrid material to obtain the polyvinyl alcohol scaffold; the artificial bone scaffold obtained based on the above polyvinyl alcohol scaffold and the amorphous calcium phosphate nano-hybrid material can achieve step-by-step degradation and improve the osteogenesis ability of the artificial bone scaffold; specifically, the polyvinyl alcohol scaffold first degrades to release the amorphous zinc phosphate material, and the amorphous zinc phosphate material quickly degrades to release zinc ions that are beneficial to angiogenesis, thereby helping early vascularization; as the implantation time increases, the infused crystalline calcium phosphate nano-hybrid material subsequently degrades and releases the amorphous calcium phosphate material that is beneficial to osteogenesis.

[0040] 3. On the other hand, the present invention provides an artificial bone scaffold obtained by the above-mentioned preparation method, wherein the artificial bone scaffold comprises a polyvinyl alcohol scaffold and an amorphous calcium phosphate nano-hybrid material infused in the pores of the polyvinyl alcohol scaffold, wherein the compressive strength is above 40 MPa and the degradation time is 12-24 months; wherein the polyvinyl alcohol scaffold is first degraded to release the amorphous zinc phosphate material, and the amorphous zinc phosphate material is rapidly degraded to release zinc ions that are beneficial to promoting angiogenesis, thereby helping early vascularization; as the implantation time is prolonged, the infused crystalline calcium phosphate nano-hybrid material is subsequently degraded and releases the amorphous calcium phosphate material that is beneficial to osteogenesis, thereby ultimately achieving rapid repair of large bone segments and load-bearing bone defects, and having important clinical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0042] Figure 1 is a microscopic morphology of amorphous zinc phosphate in Example 1;

[0043] Figure 2 is a physical picture of the polyvinyl alcohol stent in Example 1;

[0044] Figure 3 is a microscopic morphology of amorphous calcium phosphate in Example 1;

[0045] Figure 4 is a physical picture of the artificial bone scaffold in Example 1;

[0046] Figure 5 is a physical picture of the artificial bone scaffold in Example 2;

[0047] Figure 6 This is a microscopic morphology of the artificial bone scaffold in Example 2. DETAILED DESCRIPTION

[0048] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0049] The present invention provides a method for preparing an artificial bone scaffold, comprising the following steps:

[0050] The amorphous calcium phosphate nano-hybrid material is poured into the polyvinyl alcohol scaffold, so that the amorphous calcium phosphate nano-material fills the pores of the polyvinyl alcohol scaffold to obtain an artificial bone scaffold;

[0051] Specifically, the molten amorphous calcium phosphate nano-hybrid material is poured into the polyvinyl alcohol scaffold through a mold; before pouring, the amorphous calcium phosphate nano-hybrid material is heated to 60°C-180°C to melt the amorphous calcium phosphate nano-hybrid material; the pouring pressure is 0.1-2MPa; the pouring time is 0.1-3h; wherein, the mold is similar to the structure of a syringe, and during pouring, the polyvinyl alcohol scaffold is first placed in the barrel, and then the molten amorphous calcium phosphate nano-hybrid material is added into the barrel, and pressure (pouring pressure) is applied through a push rod (similar to the piston rod of a syringe) to push the amorphous calcium phosphate nano-hybrid material, so that the amorphous calcium phosphate nano-hybrid material fills the pores of the polyvinyl alcohol scaffold; wherein the polyvinyl alcohol scaffold refers to an artificial bone scaffold made of polyvinyl alcohol.

[0052] Based on the above method, the present invention fills the pores of the polyvinyl alcohol scaffold with amorphous calcium phosphate nanomaterials by perfusion, and the amorphous calcium phosphate nanohybrid material forms an interlocking structure with the polyvinyl alcohol scaffold after cooling, thereby improving the strength of the artificial bone scaffold.

[0053] In the above method, the amorphous calcium phosphate nano-hybrid material is prepared by the following method: mixing amorphous calcium phosphate, polycaprolactone, and an organic solvent to obtain the amorphous calcium phosphate nano-hybrid material;

[0054] Among them, the amorphous calcium phosphate is amorphous calcium phosphate nanoparticles; the mass ratio of amorphous calcium phosphate to polycaprolactone is 0.05-1:1; the mass ratio of the total mass of amorphous calcium phosphate and polycaprolactone to the mass ratio of the organic solvent is 1:5-10; the particle size of the amorphous calcium phosphate is 10-500nm; the number average molecular weight of polycaprolactone is 36000-100000; the organic solvent is one or more of chloroform, dimethylformamide, and dichloromethane.

[0055] Among them, the amorphous calcium phosphate nano-hybrid material obtained based on the amorphous calcium phosphate of the present invention has a smaller particle size, which is conducive to its rapid degradation and metabolism in the body.

[0056] The polyvinyl alcohol scaffold is prepared by the following method: amorphous zinc phosphate, polyvinyl alcohol and glycerol are mixed to obtain a composite material of glycerol and amorphous zinc phosphate mixture coated with polyvinyl alcohol, and the composite material is subjected to heat preservation treatment to obtain an amorphous zinc phosphate nano-hybrid material; the amorphous zinc phosphate nano-hybrid material is 3D printed and then heat-treated to obtain the polyvinyl alcohol scaffold;

[0057] Among them, the amorphous zinc phosphate is amorphous zinc phosphate nanoparticles; the particle size of the amorphous zinc phosphate is 10-500nm; in the amorphous zinc phosphate, the molar ratio of zinc ions to phosphate ions is 1.45-1.55; the alcoholysis degree of polyvinyl alcohol is 80%-99%; the weight ratio of polyvinyl alcohol and glycerol is 0.5-4:1; the weight ratio of amorphous zinc phosphate to polyvinyl alcohol is 0.01-1:1; the heat treatment temperature is 80-180℃; the heat treatment time is 6-72h; in the 3D printing process: the printing temperature is 180℃-280℃; the extrusion speed is 0.05-0.5mm / s; the moving speed of the print head is 1-15mm / s; the porosity of the polyvinyl alcohol scaffold is 20%-80%.

[0058] Among them, polyvinyl alcohol degrades quickly and has high strength, so a high-strength polyvinyl alcohol scaffold can be obtained; but polyvinyl alcohol does not have a fixed melting point, that is, it cannot be in a molten state; by adding glycerol, polyvinyl alcohol has hydroxyl groups and can be in a molten state, which is convenient for 3D printing; in addition, heat treatment of the scaffold after 3D printing can further increase the strength of the polyvinyl alcohol scaffold, thereby providing strength for the artificial bone scaffold; by preparing polyvinyl alcohol scaffolds through 3D printing, personalized artificial bones can be customized according to the patient's specific conditions, thereby improving the accuracy and effectiveness of the operation.

[0059] The artificial bone scaffold obtained based on the above-mentioned polyvinyl alcohol scaffold and amorphous calcium phosphate nano-hybrid material can achieve step-by-step degradation to improve the bone formation ability of the artificial bone scaffold; specifically, the polyvinyl alcohol scaffold is first degraded to release the amorphous zinc phosphate material, and the amorphous zinc phosphate material is rapidly degraded to release zinc ions that are beneficial to angiogenesis and help early vascularization; as the implantation time increases, the infused crystalline calcium phosphate nano-hybrid material is subsequently degraded and releases the amorphous calcium phosphate material that is beneficial to osteogenesis.

[0060] In the present application, amorphous calcium phosphate is prepared by the following method:

[0061] Step S11) dissolving a calcium inorganic salt (including but not limited to calcium chloride, calcium nitrate, etc.) in an aqueous solution containing polyacrylic acid to obtain a solution A; in the solution A, the calcium ion concentration is 0.1-1 mol / L;

[0062] Step S12) dissolving phosphate (including but not limited to sodium dihydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate) in an aqueous solution containing polyacrylic acid, and adjusting the pH to 8.0-10.0 with ammonia water to obtain solution B; in solution B, the phosphate ion concentration is 0.07-0.7 mol / L;

[0063] Step S13) Mix solution A and solution B in equal volumes, stir for 1-24 hours, and then centrifuge, collect, wash, and dry in sequence to obtain amorphous calcium phosphate.

[0064] In this application, amorphous zinc phosphate is prepared by the following method:

[0065] Step S21) dissolving a zinc inorganic salt (including but not limited to zinc chloride, zinc nitrate, etc.) in an aqueous solution containing polyacrylic acid to obtain a solution A; in the solution A, the zinc ion concentration is 0.1-1 mol / L;

[0066] Step S22) dissolving phosphate (including but not limited to sodium dihydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate) in an aqueous solution containing polyacrylic acid, and adjusting the pH to 8.0-10.0 with ammonia water to obtain solution B; in solution B, the phosphate ion concentration is 0.07-0.7 mol / L;

[0067] Step S23) Solution A and solution B are mixed in equal volumes, stirred for 1-24 hours, and then centrifuged, collected, washed, and dried in sequence to obtain amorphous zinc phosphate.

[0068] On the other hand, the present invention provides an artificial bone scaffold obtained by any of the above preparation methods, the artificial bone scaffold comprising a polyvinyl alcohol scaffold and an amorphous calcium phosphate nano-hybrid material infused into the pores of the polyvinyl alcohol scaffold; the compressive strength of the artificial bone scaffold is above 40 MPa; and the degradation time of the artificial bone scaffold is 12-24 months.

[0069] The present invention is further described below by means of specific examples and comparative examples.

[0070] Example 1

[0071] This embodiment provides a method for preparing an artificial bone scaffold, comprising the following steps:

[0072] Preparation of polyvinyl alcohol scaffold: 1 g of amorphous zinc phosphate is added to 20 g of glycerol, and ultrasonically mixed for 5 min, then 30 g of polyvinyl alcohol is added to the above mixture, and after sufficient mixing, it is placed in an 80°C oven for heat preservation for 24 h to obtain an amorphous zinc phosphate nanohybrid material; then the amorphous zinc phosphate nanohybrid material is 3D printed using a melt extrusion 3D printer to obtain a polyvinyl alcohol scaffold; the polyvinyl alcohol scaffold is vacuum heat treated to obtain a heat-treated polyvinyl alcohol scaffold;

[0073] Among them, the microstructures of amorphous zinc phosphate are as follows: Figure 1 As shown, it can be seen that the amorphous zinc phosphate is spherical with a particle size of about 80nm; the molar ratio of zinc ions to phosphate ions in the amorphous zinc phosphate is 1.45; the alcoholysis degree of polyvinyl alcohol is 80%; the weight ratio of polyvinyl alcohol to glycerol is 1.5:1; the weight ratio of amorphous zinc phosphate to polyvinyl alcohol is about 0.03:1; the heat treatment temperature is 120℃; the heat treatment time is 48h; in the 3D printing process: the printing temperature is 260℃, the diameter of the print head is 0.5mm, the moving speed of the print head is 4mm / s, and the extrusion speed is 0.05mm / s; the obtained polyvinyl alcohol scaffold is as shown in Figure 2 As shown, its porosity is 50%;

[0074] Preparation of amorphous calcium phosphate nano-hybrid material: 2.0 g of amorphous calcium phosphate was dissolved in 120 mL of dimethylformamide (organic solvent), and then 8.0 g of polycaprolactone was added to the mixture, mixed thoroughly, and then added to 1000 mL of cold water. After being fully mixed, the mixture was placed in an oven at 50° C. and dried for 24 h to obtain an amorphous calcium phosphate nano-hybrid material;

[0075] Among them, the microscopic morphology of amorphous calcium phosphate is as follows Figure 3 As shown, it can be seen that the amorphous calcium phosphate is spherical with a particle size of about 100 nm; the number average molecular weight of polycaprolactone is 36000; the mass ratio of amorphous calcium phosphate to polycaprolactone is 0.25:1, and the mass ratio of the total mass of amorphous calcium phosphate and polycaprolactone to the mass ratio of the organic solvent is 1:5; since dimethylformamide is more soluble in water, adding cold water can make polycaprolactone precipitate faster;

[0076] The amorphous calcium phosphate nano-hybrid material is placed in a vacuum at 120°C and heated for 1 hour. After it is melted, it is pressed (infused) into the heat-treated polyvinyl alcohol scaffold through a mold, so that the amorphous calcium phosphate nano-material fills the pores of the polyvinyl alcohol scaffold to obtain an artificial bone scaffold; wherein the infusion pressure is 0.5MPa; and the infusion time is 15min.

[0077] The artificial bone scaffold obtained in this embodiment is as follows Figure 4 As shown, its compressive strength is 46MPa.

[0078] Example 2

[0079] This embodiment provides a method for preparing an artificial bone scaffold, comprising the following steps:

[0080] Preparation of polyvinyl alcohol scaffold: 1 g of amorphous zinc phosphate is added to 20 g of glycerol, and ultrasonically mixed for 5 min, then 30 g of polyvinyl alcohol is added to the above mixture, and after sufficient mixing, it is placed in an 80°C oven for heat preservation for 36 h to obtain an amorphous zinc phosphate nanohybrid material; then the amorphous zinc phosphate nanohybrid material is 3D printed by a melt extrusion 3D printer to obtain a polyvinyl alcohol scaffold; the polyvinyl alcohol scaffold is vacuum heat treated to obtain a heat-treated polyvinyl alcohol scaffold;

[0081] Among them, the particle size of amorphous zinc phosphate is about 100nm; the molar ratio of zinc ions to phosphate ions in amorphous zinc phosphate is 1.55; the alcoholysis degree of polyvinyl alcohol is 99%; the weight ratio of polyvinyl alcohol to glycerol is 1.5:1; the weight ratio of amorphous zinc phosphate to polyvinyl alcohol is about 0.03:1; the heat treatment temperature is 160°C; the heat treatment time is 48h; in the 3D printing process: the printing temperature is 240°C, the diameter of the print head is 0.3mm, the moving speed of the print head is 8mm / s, and the extrusion speed is 0.1mm / s; the porosity of the obtained polyvinyl alcohol scaffold is 30%;

[0082] Preparation of amorphous calcium phosphate nano-hybrid material: 2.0 g of amorphous calcium phosphate was dissolved in 120 mL of dimethylformamide (organic solvent), and then 8.0 g of polycaprolactone was added to the mixture, mixed thoroughly, and then added to 1000 mL of cold water. After being fully mixed, the mixture was placed in an oven at 50° C. and dried for 24 h to obtain an amorphous calcium phosphate nano-hybrid material;

[0083] The particle size of amorphous calcium phosphate is about 100 nm; the number average molecular weight of polycaprolactone is 100,000; the mass ratio of amorphous calcium phosphate to polycaprolactone is 0.25:1, and the mass ratio of the total mass of amorphous calcium phosphate and polycaprolactone to the mass ratio of the organic solvent is 1:10; since dimethylformamide is more soluble in water, adding cold water can make polycaprolactone precipitate faster;

[0084] The amorphous calcium phosphate nano-hybrid material is placed in a vacuum at 120°C and heated for 1 hour. After it is melted, it is pressed (infused) into the heat-treated polyvinyl alcohol scaffold through a mold, so that the amorphous calcium phosphate nano-material fills the pores of the polyvinyl alcohol scaffold to obtain an artificial bone scaffold; wherein the infusion pressure is 0.5MPa; and the infusion time is 15min.

[0085] The artificial bone scaffold obtained in this embodiment is as follows Figure 5 Its microscopic morphology is as shown in Figure 6As shown, the compressive strength of the artificial bone scaffold of this embodiment is measured to be 56 MPa.

[0086] Comparative Example 1

[0087] This comparative example provides a method for preparing an artificial bone scaffold, comprising the following steps:

[0088] Preparation of polyvinyl alcohol scaffold: 1 g of amorphous zinc phosphate is added to 20 g of glycerol, and ultrasonically mixed for 5 min, then 30 g of polyvinyl alcohol is added to the above mixture, and after sufficient mixing, it is placed in an 80°C oven for heat preservation for 24 h to obtain an amorphous zinc phosphate nanohybrid material; then the amorphous zinc phosphate nanohybrid material is 3D printed using a melt extrusion 3D printer to obtain a polyvinyl alcohol scaffold; the polyvinyl alcohol scaffold is vacuum heat treated to obtain a heat-treated polyvinyl alcohol scaffold;

[0089] Among them, the particle size of amorphous zinc phosphate is about 80nm; the molar ratio of zinc ions to phosphate ions in amorphous zinc phosphate is 1.45; the alcoholysis degree of polyvinyl alcohol is 80%; the weight ratio of polyvinyl alcohol to glycerol is 1.5:1; the weight ratio of amorphous zinc phosphate to polyvinyl alcohol is about 0.03:1; the heat treatment temperature is 70°C; the heat treatment time is 48h; in the 3D printing process: the printing temperature is 260°C, the diameter of the print head is 0.5mm, the moving speed of the print head is 4mm / s, and the extrusion speed is 0.05mm / s; the porosity of the obtained polyvinyl alcohol scaffold is 50%;

[0090] Preparation of amorphous calcium phosphate nano-hybrid material: 2.0 g of amorphous calcium phosphate was dissolved in 120 mL of dimethylformamide (organic solvent), and then 8.0 g of polycaprolactone was added to the mixture, mixed thoroughly, and then added to 1000 mL of cold water. After being fully mixed, the mixture was placed in an oven at 50° C. and dried for 24 h to obtain an amorphous calcium phosphate nano-hybrid material;

[0091] The particle size of amorphous calcium phosphate is about 100 nm; the number average molecular weight of polycaprolactone is 36,000; the mass ratio of amorphous calcium phosphate to polycaprolactone is 0.25:1, and the mass ratio of the total mass of amorphous calcium phosphate and polycaprolactone to the mass ratio of the organic solvent is 1:5; since dimethylformamide is more soluble in water, adding cold water can make polycaprolactone precipitate faster;

[0092] The amorphous calcium phosphate nano-hybrid material is placed in a vacuum at 120°C and heated for 1 hour. After it is melted, it is pressed (infused) into the heat-treated polyvinyl alcohol scaffold through a mold, so that the amorphous calcium phosphate nano-material fills the pores of the polyvinyl alcohol scaffold to obtain an artificial bone scaffold; wherein the infusion pressure is 0.5MPa; and the infusion time is 15min.

[0093] The compressive strength of the artificial bone scaffold obtained in this comparative example is 18 MPa. Since the heat treatment temperature is 70°C, which is much lower than 120°C in Example 1, the degree of etherification of the 3D printed polyvinyl alcohol scaffold is relatively low, and the ether bond can improve the strength of the material. Therefore, the strength of the polyvinyl alcohol scaffold in Example 1 is higher than that of the polyvinyl alcohol scaffold in Comparative Example 1, so the strength of the artificial bone scaffold after perfusion is higher.

[0094] Comparative Example 2

[0095] This comparative example provides a method for preparing an artificial bone scaffold, comprising the following steps:

[0096] Preparation of polyvinyl alcohol scaffold: 1 g of amorphous zinc phosphate is added to 20 g of glycerol, and ultrasonically mixed for 5 min, then 30 g of polyvinyl alcohol is added to the above mixture, and after sufficient mixing, it is placed in an 80°C oven for heat preservation for 36 h to obtain an amorphous zinc phosphate nanohybrid material; then the amorphous zinc phosphate nanohybrid material is 3D printed by a melt extrusion 3D printer to obtain a polyvinyl alcohol scaffold; the polyvinyl alcohol scaffold is vacuum heat treated to obtain a heat-treated polyvinyl alcohol scaffold;

[0097] Among them, the particle size of amorphous zinc phosphate is about 100nm; the molar ratio of zinc ions to phosphate ions in amorphous zinc phosphate is 1.55; the alcoholysis degree of polyvinyl alcohol is 99%; the weight ratio of polyvinyl alcohol to glycerol is 1.5:1; the weight ratio of amorphous zinc phosphate to polyvinyl alcohol is about 0.03:1; the heat treatment temperature is 160°C; the heat treatment time is 48h; in the 3D printing process: the printing temperature is 240°C, the diameter of the print head is 0.3mm, the moving speed of the print head is 8mm / s, and the extrusion speed is 0.1mm / s; the porosity of the obtained polyvinyl alcohol scaffold is 30%;

[0098] Preparation of amorphous calcium phosphate nano-hybrid material: 2.0 g of amorphous calcium phosphate was dissolved in 120 mL of dimethylformamide (organic solvent), and then 8.0 g of polycaprolactone was added to the mixture, mixed thoroughly, and then added to 1000 mL of cold water. After being fully mixed, the mixture was placed in an oven at 50° C. and dried for 24 h to obtain an amorphous calcium phosphate nano-hybrid material;

[0099] The particle size of amorphous calcium phosphate is about 100 nm; the number average molecular weight of polycaprolactone is 100,000; the mass ratio of amorphous calcium phosphate to polycaprolactone is 0.25:1, and the mass ratio of the total mass of amorphous calcium phosphate and polycaprolactone to the mass ratio of the organic solvent is 1:10; since dimethylformamide is more soluble in water, adding cold water can make polycaprolactone precipitate faster;

[0100] The amorphous calcium phosphate nano-hybrid material was placed in a vacuum at 50° C. and heated for 1 hour. The amorphous calcium phosphate nano-hybrid material could not reach the melting point temperature (60° C.) of the amorphous calcium phosphate nano-hybrid material, causing the polycaprolactone material to be unable to melt, and thus infusion could not be performed.

[0101] It is easy for those skilled in the art to understand that, without conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.

[0102] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present invention. These improvements and variations should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an artificial bone scaffold, characterized in that: The following steps are involved: The amorphous calcium phosphate nano-hybrid material is infused into the polyvinyl alcohol scaffold, so that the amorphous calcium phosphate nano-material fills the pores of the polyvinyl alcohol scaffold to obtain the artificial bone scaffold.

2. The method for preparing an artificial bone scaffold according to claim 1, characterized in that: The amorphous calcium phosphate nano-hybrid material is prepared by the following method: Mixing amorphous calcium phosphate, polycaprolactone and an organic solvent to obtain the amorphous calcium phosphate nano-hybrid material; Wherein, the amorphous calcium phosphate is amorphous calcium phosphate nanoparticles.

3. The method for preparing an artificial bone scaffold according to claim 2, characterized in that: The mass ratio of the amorphous calcium phosphate to the polycaprolactone is 0.05-1:1; and / or The mass ratio of the total mass of the amorphous calcium phosphate and the polycaprolactone to the mass of the organic solvent is 1:5-10; and / or The particle size of the amorphous calcium phosphate is 10-500 nm; and / or The number average molecular weight of the polycaprolactone is 36000-100000; and / or The organic solvent is one or more of chloroform, dimethylformamide and dichloromethane.

4. The method for preparing an artificial bone scaffold according to any one of claims 1 to 3, characterized in that: The polyvinyl alcohol scaffold is prepared by the following method: Amorphous zinc phosphate, polyvinyl alcohol and glycerol are mixed, and after heat preservation treatment, an amorphous zinc phosphate nano-hybrid material is obtained, and the amorphous zinc phosphate nano-hybrid material is 3D printed to obtain the polyvinyl alcohol scaffold; Wherein, the amorphous zinc phosphate is amorphous zinc phosphate nanoparticles.

5. The method for preparing an artificial bone scaffold according to claim 4, characterized in that: The particle size of the amorphous zinc phosphate is 10-500 nm; and / or In the amorphous zinc phosphate, the molar ratio of zinc ions to phosphate ions is 1.45-1.55; and / or The alcoholysis degree of the polyvinyl alcohol is 80%-99%; and / or The weight ratio of polyvinyl alcohol to glycerol is 0.5-4:1; and / or The weight ratio of the amorphous zinc phosphate to the polyvinyl alcohol is 0.01-1:

1.

6. The method for preparing an artificial bone scaffold according to claim 4, characterized in that: During the 3D printing process: the printing temperature is 180°C-280°C; the extrusion speed is 0.05-0.5 mm / s; the moving speed of the print head is 1-15 mm / s; and / or The porosity of the polyvinyl alcohol scaffold is 20%-80%.

7. The method for preparing an artificial bone scaffold according to claim 4, characterized in that: After the step of 3D printing the amorphous zinc phosphate nano-hybrid material, the method further comprises: heat treating the polyvinyl alcohol stent; Preferably, the temperature of the heat treatment is 80-180°C; Preferably, the heat treatment time is 6-72h.

8. The method for preparing an artificial bone scaffold according to claim 1, characterized in that: Infusing the amorphous calcium phosphate nano-hybrid material into the polyvinyl alcohol stent through a mold; wherein the amorphous calcium phosphate nano-hybrid material is in a molten state; Preferably, before pouring, the amorphous calcium phosphate nano-hybrid material is heated to 60° C.-180° C.; Preferably, the perfusion pressure is 0.1-2MPa; Preferably, the perfusion time is 0.1-3h.

9. An artificial bone scaffold, characterized in that: The artificial bone scaffold comprises a polyvinyl alcohol scaffold and an amorphous calcium phosphate nano-hybrid material infused into the pores of the polyvinyl alcohol scaffold; The compressive strength of the artificial bone scaffold is above 40MPa; The degradation time of the artificial bone scaffold is 12-24 months.

10. The artificial bone scaffold according to claim 9, characterized in that: The artificial bone scaffold is obtained by the preparation method according to any one of claims 1 to 8.